The tyrosyl-DNA phosphodiesterase Tdp1 is a member of the phospholipase D superfamily - Interthal, Heidrun (The National Academy of Sciences, 2001)
The phospholipase D (PLD) superfamily is a diverse group of proteins that includes enzymes involved in phospholipid metabolism, a bacterial toxin, poxvirus envelope proteins, and bacterial nucleases. Based on sequence comparisons, we show here that the tyrosyl-DNA phosphodiesterase (Tdp1) that has been implicated in the repair of topoisomerase I covalent complexes with DNA contains two unusual HKD signature motifs that place the enzyme in a distinct class within the PLD superfamily. Mutagenesis studies with the human enzyme in which the invariant histidines and lysines of the HKD motifs are changed confirm that these highly conserved residues are essential for Tdp1 activity. Furthermore, we show that, like other members of the family for which it has been examined, the reaction involves the formation of an intermediate in which the cleaved substrate is covalently linked to the enzyme. These results reveal that the hydrolytic reaction catalyzed by Tdp1 occurs by the phosphoryl transfer chemistry that is common to all members of the PLD superfamily.